Working Time of Women in Natural Silk Agribusiness in Soppeng Regency - Rahmadanih, Rahmadanih; Bulkis, Sitti; Ashar, Nurul Magfirah; Busthanul, Nurbaya; Tenriawaru, A. Nixia (Hasanuddin University, 2024)
Natural silk is an agro-industrial activity that includes aspects of cultivation and related industrial aspects. This study aims to determine and analyze women's time allocation for each activity in the natural silk agribusiness business in Soppeng Regency. The research was conducted from December 2021 to January 2022 in Donri-Donri and Lilirilau Districts, Soppeng Regency. The research method used is descriptive with a quantitative approach. Data were obtained through field observations, interviews and by distributing questionnaires. The results obtained are the outpouring of working time based on the analysis of working people's days in mulberry cultivation activities, the working time range is 1-3 hours/day having an average working time of 4.05 HOK, silkworm cultivation activities have a working time span of 5-8 hours/day has an average working time of 5.05 HOK, spinning cultivation activities have a working time of 4 – 10 hours/day has an average working time of 0.09 HOK, weaving activities work time span of 4 – 6 hours /day has an average working time of 0.09 HOK, and distribution and marketing activities with a working time span of 8 hours/day has an average working time of 13.04 HOK. The time spent on each sub-system activity in natural silk agribusiness is different because it is influenced by each process carried out in the course of the activity.